Implementation of Renewable Energy-based Public Wireless Internet Infrastructure in Rural Indonesia - Nurchim; Wijiyanto (Proceeding of International Conference on Science, Health, And Technology, 2021)
The provision of the internet as an effort to encourage digitalization in rural areas is expected to provide opportunities for rural economic development, employment opportunities, trade, and other conveniences. Implementation of the internet in this rural area is a challenging task especially concerning geographic conditions such as hilly environments, lots of trees, and the location of the nearest broadcast station. Besides, the internet as a public infrastructure in rural areas must be combined with renewable energy to prevent environmental pollution and cost-efficiency. This study aims to analyze the provision of renewable energy-based public internet infrastructure in rural Indonesia using an applied research approach. Public internet infrastructure is developed with a wireless model using solar PV as a source of electrical energy. The results state that the provision of renewable energy-based internet has received a positive response from the village community because it provides easy wireless connectivity. However, there are still a few villagers who use the internet for productive purposes.